2008
DOI: 10.1021/jf073317s
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Solubilization of Proteins in Brewer’s Spent Grain

Abstract: Brewer's spent grain (BSG) is an abundant, protein-rich coproduct from the beer industry. There is a growing interest in increasing and diversifying the exploitation of BSG and related coproducts for economic and environmental reasons. In this paper, we report on a study of the solubilization of proteinaceous material from BSG using several commercial peptidase preparations. Our data show that Alcalase is the most effective peptidase for solubilization of BSG proteins, with an ability to release up to 77% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 31 publications
(48 reference statements)
7
39
0
Order By: Relevance
“…Finally, at 24 h hydrolysis time, the DH was 21.80 AE 2.32%. Similar DHs were obtained by Treimo, Aspmo, Eijsinkm, and Hornm (2008). Contrarily, this DH value was higher that the previously value achieved with BSG hydrolysates by Celus, Brijs, and Delucour (2009), who hydrolysed a chemically isolated protein concentrate.…”
Section: Hydrolysates Preparationsupporting
confidence: 87%
“…Finally, at 24 h hydrolysis time, the DH was 21.80 AE 2.32%. Similar DHs were obtained by Treimo, Aspmo, Eijsinkm, and Hornm (2008). Contrarily, this DH value was higher that the previously value achieved with BSG hydrolysates by Celus, Brijs, and Delucour (2009), who hydrolysed a chemically isolated protein concentrate.…”
Section: Hydrolysates Preparationsupporting
confidence: 87%
“…However, an earlier study by this group demonstrated that inhibition of proteolytic activity in an enzyme preparation that had both carbohydrase and protease activities (Depol 740) only resulted in a 5% decrease in BSG solubilisation, suggesting that proteolytic activity is not essential (32). It was shown that 77% of the proteinaceous material in BSG could be solubilised with Alcalase, using a simple enzymatic hydrolysis step (34). Alcalase (protease from Bacillus licheniformis, Novozymes A/S) has been shown to be a very effective protease for solubilisation of BSG proteins.…”
Section: Spoilage Of Bsg and Methods Of Preservationmentioning
confidence: 99%
“…Feruloyl esterase activity has been measured in faecal samples 30 and in commensal bacteria 14,51 . The protein content of the hydrolysis residue could be minimized by combining an efficient protease to the process 50 . The lignin type residue could be used for an energy source or the properties of the lignin type material could be exploited in other applications.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic hydrolysis is a potential method to solubilise BSG components for further fractionation due to the specificity and mild reaction conditions needed. Enzymatic hydrolysis of BSG has been investigated in order to solubilise proteins by proteolytic enzymes 13,32,50 , xylooligosaccharides by xylanases 28 , glucose by a mixture of hydrolases 37 or FA with feruloyl esterase either alone or together with xylanase 5,18 . Trichoderma enzymes have also been used to increase the amount of soluble dietary fibre in BSG 39 .…”
Section: Introductionmentioning
confidence: 99%